2021
DOI: 10.2217/fmb-2020-0243
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Bacterial DNA Presence in Chorionic Villi and Amniotic Fluid in the First and Second Trimester of Pregnancy

Abstract: The sterile-womb dogma in uncomplicated pregnancy has been lively debated. Data regarding the in utero microbiome environment are based mainly on studies performed at the time of delivery. Aim: To determine whether human placenta and amniotic fluid are populated by a bacterial microbiota in the first and second trimesters of pregnancy. Materials & methods: We analyzed by next-generation sequencing method 24 and 29 samples from chorionic villus sampling (CVS) and amniocentesis (AC), respectively. The V3 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…are resident microbiota of mammals, including humans and mice (122,(143)(144)(145). However, these microorganisms have also been identified as common bacterial DNA contaminants in studies with low microbial biomass (98,103,132). Corynebacterium spp.…”
Section: Our Findings In the Context Of Prior Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…are resident microbiota of mammals, including humans and mice (122,(143)(144)(145). However, these microorganisms have also been identified as common bacterial DNA contaminants in studies with low microbial biomass (98,103,132). Corynebacterium spp.…”
Section: Our Findings In the Context Of Prior Studiesmentioning
confidence: 99%
“…Investigations of human amniotic fluid in normal pregnancy have yielded contradictory results. Multiple studies using DNA sequencing techniques (75,84,85,(96)(97)(98) and/or quantitative real-time PCR (83,97) have identified a molecular signal indicating the presence of an amniotic fluid microbiota; however, only one of these studies has demonstrated viable microorganisms from amniotic fluid through culture (75) (Supplementary Table 1). To date, no study has used cultivation, qPCR, and DNA sequencing concurrently to confirm the existence of a microbiota in human amniotic fluid during normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “ microbiota ” identifies all microorganisms, mainly bacteria and a small number of fungi, archaea, and viruses, that live on the surface and inside our body ( D’Argenio and Salvatore, 2015 ). Most of the adult human microbiota lives in the gut but it also colonizes the oral cavity, skin, vagina, and the lung ( Dickson et al, 2016 ; Blum, 2017 ; Maschirow et al, 2019 ; Campisciano et al, 2021 ). These communities of microorganisms are essential for human physiology and survival and for this reason the microbiota is called the “forgotten organ” ( O’Hara and Shanahan, 2006 ).…”
Section: The Microbiota As a Modulator Of Leptin Sensitivitymentioning
confidence: 99%
“…At birth, the neonates of viviparous mammals move abruptly from a (near) sterile environment (Perez-Munoz et al, 2017;Lim et al, 2018;Rehbinder et al, 2018;Stinson et al, 2019;Campisciano et al, 2020;Singh and Mittal, 2020) of their mothers' uteri into a world rich in potential pathogens. The survival of neonates depends on both their endogenous innate and newly engaged adaptive immune systems, and, more immediately, antibodies passively acquired from their mothers (Brambell, 1970).…”
Section: Introductionmentioning
confidence: 99%